2018
DOI: 10.1111/azo.12251
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the eye tunics, eyelids and ocular glands of the Sulawesi bear cuscus (Ailurops ursinusTemminck, 1824) (Phalangeridae: Marsupialia) based on anatomical, histological and histochemical studies

Abstract: This study described the anatomy, histology and the histochemical analysis of the eye tunics, the upper and lower eyelid, the third eyelid, the lacrimal gland and the superficial gland of the third eyelid in adult Sulawesi bear cuscus. The eyeball and the eyelids with the orbital glands were harvested immediately post‐mortem. The eyeball in the Sulawesi bear cuscus had a sphere‐like shape. The pupil was round, and the lens was a circular biconvex body. There was neither tapetum lucidum nor Harderian gland. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 123 publications
(260 reference statements)
0
6
0
Order By: Relevance
“…However, the study of Nawrot et al (2019) found no tapetum lucidum in the eyes of A. ursinus. Tapetum lucidum as a biological reflector system, is a feature of vertebrate eyes and serves to reflect photons to the retina thereby increasing visual sensitivity at low light levels, this is an advantage for nocturnal animals (Ollivier et al 2004;Kay et al 2004).…”
Section: Activity Patternmentioning
confidence: 90%
“…However, the study of Nawrot et al (2019) found no tapetum lucidum in the eyes of A. ursinus. Tapetum lucidum as a biological reflector system, is a feature of vertebrate eyes and serves to reflect photons to the retina thereby increasing visual sensitivity at low light levels, this is an advantage for nocturnal animals (Ollivier et al 2004;Kay et al 2004).…”
Section: Activity Patternmentioning
confidence: 90%
“…The copyright holder for this preprint this version posted August 22, 2022. ; https://doi.org/10.1101/2022.08.20.504636 doi: bioRxiv preprint who's confirmed the lower eyelid of bird is more mobile than upper one (Wyneken, 2012). That feature is common in mammals; the upper eyelid is more mobile and larger than the lower eyelid (Klećkowska-Nawrot et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…The movement of upper eyelid in little owl is opposite the views of most previous authors who’s confirmed the lower eyelid of bird is more mobile than upper one (Wyneken, 2012). That feature is common in mammals; the upper eyelid is more mobile and larger than the lower eyelid (Klećkowska-Nawrot et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The movement of the upper eyelid in little owl is opposite to the views of most previous authors who confirmed that the lower eyelid of birds is more mobile than the upper one. That feature is common in mammals; the upper eyelid is more mobile and larger than the lower eyelid (Klećkowska‐Nawrot et al, 2019).…”
Section: Discussionmentioning
confidence: 99%